2020
DOI: 10.31620/jccc.12.20/09
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Ott Video Streaming Platforms in India During Covid -19: Extending Utaut2 With Content Availability

Abstract: The paper aims at identifying factors that stimulates the customers to adopt and use OTT video streaming platforms in India by applying unified theory of acceptance and use of technology 2 (UTAUT2) model. The study has also attempted to check the moderation effect of age, gender, experience. The study uses a questionnaire to gather the primary data of 277 users of OTT video streaming platforms of India as respondents. The data was examined using SmartPLS 3.3.2 software. The key drivers of adopting and using OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…At the face of COVID-19 and lockdowns, isolated individuals found Netflix an alternative means of entertainment to actual parties and gatherings with people. Furthermore, they actively participated in virtual communities where they exchanged their thoughts, knowledge, emotions and affections with strangers based on their binge watching of Netflix content (de Oliveira Dias, 2020; Gupta and Singharia, 2021; Malewar and Bajaj, 2020; Patel et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the face of COVID-19 and lockdowns, isolated individuals found Netflix an alternative means of entertainment to actual parties and gatherings with people. Furthermore, they actively participated in virtual communities where they exchanged their thoughts, knowledge, emotions and affections with strangers based on their binge watching of Netflix content (de Oliveira Dias, 2020; Gupta and Singharia, 2021; Malewar and Bajaj, 2020; Patel et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One such external source of the accidental discovery of new value of knowledge is the pandemic situation. As several studies have already reported (see inter alia, Anand and Srinivas, 2020;Gupta and Singharia, 2021;Malewar and Bajaj, 2020;Patel et al, 2020;Tripathi, 2020;Vlassis, 2021), the number of registered members of Netflix has exponentially increased during the COVID-19 pandemic in the countries where the online streaming or over-the-top (OTT) service is provided, especially between 2020 and 2021. These reports, however, have not yet produced any systemic empirical analysis on the cause of this accidental upsurge in the use of Netflix during the lockdown.…”
Section: Introductionmentioning
confidence: 98%
“…Research studies in past have concluded in their findings that "Content" is the most pertinent reason for shaping the users' attitude towards subscribing to an OTT platform. (Malewar and Bajaj.,2020) in their study highlight some important features of OTT influencing consumer adoption such as comfort, ease of use, pleasure, etc. Among all other features, they stressed the uniqueness of OTT content which makes it distinctive, attracts users, and is the strongest reason for its adoption.…”
Section: Previous Research On the Impact Of Consumers' Attitudes On P...mentioning
confidence: 99%
“…The outbreak has forced consumers to replace viewing big-screen movies at theaters temporarily with OTT platforms; as a result, a high proportion of viewers have formed the habit of watching movies on streaming platforms (Revati Devaki and Babu, 2021). Their new viewing habits have become the new normal (Malewar and Bajaj, 2020). Most OTT providers initially attract consumers by offering a free trial period, after which consumers pay a fixed monthly fee for unlimited access to all of the streaming platform's contents (Gupta and Singharia, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Shin and Park (2021) also discovered that OTT users, as a consideration in choosing the viewing media, pursue social interaction with others, pleasant user experiences, diverse content, easy and convenient access, reliable service system quality, and a positive perception of price value. Malewar and Bajaj (2020) showed that content availability, facilitating conditions, and habit significantly impact the use of streaming technology and that price value perceived by consumers plays a vital role in the adoption of OTT platforms. Madnani et al (2020) concluded that the convenience of high-quality, ad-free digital content gradually shifted consumer preferences from traditional TV to OTT platforms.…”
Section: Introductionmentioning
confidence: 99%